Marketing Strategy Analysis of Okra Leaf Guest House Syariah Bontang to Improve Competitiveness - Bustami, Abiyajid; Maulidina, Rizky Awaliyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The competition in the sharia hotel industry is growing, driven by increasing interest in halal tourism, which emphasizes services aligned with Islamic principles. Okra Leaf Guest House Syariah in Bontang, a sharia-based accommodation, faces challenges in boosting its competitiveness. This study analyzes the marketing strategies applied by Okra Leaf to strengthen its position using a case study approach involving semi-structured interviews, participatory observation, and document analysis. The findings show that Okra Leaf differentiates its services through sharia principles, such as prayer facilities and halal food, which have been positively received by customers. However, digital marketing and customer relationship management (CRM) remain underutilized. The SWOT analysis highlights the strength of authentic sharia services, while digital infrastructure is identified as a weakness. The study recommends improving digital marketing and optimizing CRM to enhance competitiveness. Implementing these strategies can help Okra Leaf expand its market and increase customer loyalty.